Factors associated with persistent positive in HBV DNA level in patients with chronic Hepatitis B receiving entecavir treatment - Li, Jun; Dong, Xiao-Qin; Cao, Li-Hua; Zhang, Zhan-Qing; Zhao, Wei-Feng; Shang, Qing-Hua; Zhang, Da-Zhi; Ma, An-Lin; Xie, Qing; Gui, Hong-Lian; Zhang, Guo; Liu, Ying-Xia; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction The clinical significance of persistent positive in Hepatitis B Virus (HBV) DNA level in patients receiving antiviral therapy is not well known. We investigated factors associated with persistent viremia (PV) in patients with chronic hepatitis B (CHB) given 78-week entecavir. Methods A total of 394 treatment-naïve CHB patients who had undergone liver biopsy at baseline and week 78 of treatment were analyzed in this prospective multicentre study. We identified patients with PV (above the lower limit of quantification, 20 IU/ml) after 78 weeks of entecavir therapy. Stepwise, forward, multivariate regression analyses of specified baseline parameters were apllied to identify factors associated with PV. Futhermore, we assessed the incidence of hepatocellular carcinoma (HCC) in all patients using models of the risk of HCC development. Results Of the 394 patients, 90 (22.8%) still with PV after 78-week antiviral treatment. Factors associated significantly with PV (vs complete virological response, CVR) were HBV DNA level ≥8 log10 IU/mL (OR, 3.727; 95% CI, 1.851-7.505; P < 0.001), Anti-HBc level < 3 log10 IU/mL (OR, 2.384; 95% CI, 1.223-4.645; P=0.011), and HBeAg seropositivity (OR, 2.871; 95% CI, 1.563-5.272; P < 0.001). Patients with PV were less likely to have fibrosis progression and HCC development than those with the CVR. Of the 11 HBeAg-positive patients with HBV DNA level ≥8 log10 IU/mL and Anti-HBc level < 3 log10 IU/mL at baseline, 9 (81.8%) had persistent positivity in HBV DNA level and 0 had fibrosis progression at week 78 of treatment. Discussion In conclusion, HBV DNA level ≥8 log10 IU/mL, Anti-HBc level < 3 log10 IU/mL and HBeAg seropositivity at baseline contribute to PV in patients with CHB receiving 78-week antiviral treatment. In addition, the rate of fibrosis progression and the risk of HCC development in patients with PV were kept low. The complete protocol for the clinical trial has been registered at clinicaltrials.gov (NCT01962155 and NCT03568578).